Control of a microfluidic separation process governed by the Zweifach-Fung effect. Issue 7 (2022) - Petit, Nicolas
Abstract: This paper presents a microfluidic process of separation of a fluid containing particles. The control input is the ratio of flowrates in the two daughter channels of a bifurcation, which due to the Zweifach-Fung effect, has a direct but nonlinear effect on the particle volume fractions in the channels. The dead-volumes of the device and its capillary tubings cause an input-varying delay of hydraulic type. The paper presents several control problems of practical importance and formulates some concise problem statements for future research along with first simulation results.